2021
DOI: 10.1177/15353702211003511
|View full text |Cite
|
Sign up to set email alerts
|

Variable number tandem repeats – Their emerging role in sickness and health

Abstract: Understanding the mechanisms regulating tissue specific and stimulus inducible regulation is at the heart of understanding human biology and how this translates to wellbeing, the ageing process, and disease progression. Polymorphic DNA variation is superimposed as an extra layer of complexity in such processes which underpin our individuality and are the focus of personalized medicine. This review focuses on the role and action of repetitive DNA, specifically variable number tandem repeats and SINE-VNTR- Alu d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…The latter variation affects age of onset in XDP [42]. VNTRs more generally have been studied extensively as both biomarkers and functional elements in the context of complex genetics for many years, and these elements have been shown to have tissue-specific and stimulus-inducible regulatory properties, which are modified further by polymorphism in the VNTR itself [43]. We would expect such polymorphism to play a role in the variable function of the RIP on gene expression in that it is not solely due to the presence/absence of polymorphism but also the RIP sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The latter variation affects age of onset in XDP [42]. VNTRs more generally have been studied extensively as both biomarkers and functional elements in the context of complex genetics for many years, and these elements have been shown to have tissue-specific and stimulus-inducible regulatory properties, which are modified further by polymorphism in the VNTR itself [43]. We would expect such polymorphism to play a role in the variable function of the RIP on gene expression in that it is not solely due to the presence/absence of polymorphism but also the RIP sequence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that VNTRs can be both biomarkers for disease risk and also functional regulatory domains affecting both transcription and post-transcriptional mechanisms as reviewed recently (Marshall et al, 2021 ). These latter transcriptional properties can be exhibited together for the same VNTR as in the case of the monoamine oxidase A ( MAOA ) gene (Manca et al, 2018 ) and a VNTR in the mir137 gene (Warburton et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 6 These functional studies have shown that TEs like Alu repeats, LINE1s, and composite SINE-VNTR-Alu (SVA) can modify gene expression and be a part of the disease mechanism. 7,8 Most importantly, analysis of the variability of the TEs offers a unique opportunity to identify the hidden genetic mechanisms of disease, often referred simply as the missing heritability. 9 Genome-wide association studies (GWAS) based on single nucleotide polymorphism (SNP) genotyping have enjoyed significant success in defining the genetics of complex diseases.…”
Section: Introductionmentioning
confidence: 99%